Management of blood lipids in post-kidney transplant patients: a systematic review and network meta-analysis - Luo, Bohan; Zhong, Shan; Wang, Xiaoxiao; Guo, Pu; Hou, Yifu; Di, Wenjia (Frontiers in Pharmacology, 2024)
Introduction: this meta-analysis was to evaluate the effectiveness and safety of lipid-lowering medication therapy in post-kidney transplant (PKT) patients. Material and Methods: randomized controlled trials investigating different treatment regimens (DTRs) for regulating lipid levels in PKT patients were systematically retrieved from PubMed, Cochrane Library, and Embase, from inception to March 2024. Literature quality was assessed employing the Cochrane risk of bias assessment tool. Data analysis and graphical representation were performed employing RevMan5.3 and Stata 20.0. The surface under the cumulative ranking area (SUCRA) compared the effects of DTRs on lipid profiles, incidence of adverse events, and all-cause mortality in PKT patients. Conclusion: in reducing lipid levels in PKT patients, combination therapy with statins and ezetimibe demonstrated notable advantages and higher effectiveness. PCSK9 inhibitors exhibited greater advantages in reducing adverse events and mortality rates in PKT patients, with higher safety.